Jerat Hutang Luar Negeri Pemerintah dan BUMN Indonesia - Nur Feriyanto (Universitas Islam Indonesia, 2001)
Incapability of the Indonesian government to provide sufficient fund for the development process of the country, forces it to get financial support from foreign debts. Statistical figures indicate that formany decades, the amount of the foreign debts raises dramatically. As a result, the-country then is trapped in the very deep foreign debts in which the country is very difficult to escape.